2007
DOI: 10.1001/archinte.167.6.591
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Improving the Quality of Osteoporosis Care for Long-term Glucocorticoid Users

Abstract: Background: In light of widespread undertreatment for glucocorticoid-induced osteoporosis (GIOP), we designed a group randomized controlled trial to increase bone mineral density (BMD) testing and osteoporosis medication prescribing among patients receiving longterm glucocorticoid therapy.Methods: Using administrative databases of a large US health plan, we identified physicians who prescribed longterm glucocorticoid therapy to at least 3 patients. One hundred fifty-three participating physicians were randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 28 publications
1
73
1
1
Order By: Relevance
“…Osteoporosis quality improvement interventions that principally target only the physician are likely to have only a modest impact, at best. (11) Systems-based interventions such as allowing selfreferral of at-risk persons, as has been shown to be successful for mammography, (12) may be useful to increase DXA use rates. Developing customized, patient-directed interventions that consider factors described in the Health Belief Model, perhaps in conjunction with absolute fracture risk estimates, may provide added benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoporosis quality improvement interventions that principally target only the physician are likely to have only a modest impact, at best. (11) Systems-based interventions such as allowing selfreferral of at-risk persons, as has been shown to be successful for mammography, (12) may be useful to increase DXA use rates. Developing customized, patient-directed interventions that consider factors described in the Health Belief Model, perhaps in conjunction with absolute fracture risk estimates, may provide added benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Available antiosteoporosis pharmaceutical (AOP) therapies have been shown to reduce BMD loss (16 -19), but retrospective studies have shown that Ͻ40% of patients treated chronically (Ն90 days) with glucocorticoids received an AOP (20 -25). To improve care received by glucocorticoid users, interventions and quality measures encouraging the use of AOP and BMD testing have been proposed and implemented, although their long-term effect on reducing fractures is not known (22,(25)(26)(27)(28). These interventions could reduce the care gap in patients treated with glucocorticoids, potentially decreasing the incidence of fracture and fracture-related morbidity in this high-risk patient population.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] While decision-making related to bisphosphonates involves difficult trade-offs among the potential benefits, known toxicity and unknown long-term effects, studies have also documented underuse of calcium and vitamin D supplementation. A review found that approximately 30 % of patients at a large health maintenance organization in the U.S. on glucocorticoids received calcium and vitamin D. 8 In 2002, Solomon et al 9 examined management practices for patients with rheumatoid arthritis taking glucocorticoids at one academic medical rheumatology practice and found that only 25 % of patients had calcium and/or vitamin D recorded on the medication list.…”
Section: Introductionmentioning
confidence: 99%
“…A review found that approximately 30 % of patients at a large health maintenance organization in the U.S. on glucocorticoids received calcium and vitamin D. 8 In 2002, Solomon et al 9 examined management practices for patients with rheumatoid arthritis taking glucocorticoids at one academic medical rheumatology practice and found that only 25 % of patients had calcium and/or vitamin D recorded on the medication list. Curtis et al 10 reviewed a database of patients on glucocorticoids from a national managed care organization and reported that 51 % of physicians, across all specialties, prescribed calcium and vitamin D, and 55 % of rheumatologists prescribed calcium and vitamin D. A retrospective chart review of 100 patients receiving long-term glucocorticoids at an academic Veterans Affairs (VA) Medical Center revealed that 32 patients were prescribed calcium supplementation and 12 patients were prescribed vitamin D. 11 Several interventions have been developed to improve adherence to recommendations to prevent GIOP. [12][13][14] At one US academic center, a trial randomized 21 rheumatologists caring for 373 chronic glucocorticoid users to an intervention consisting of a lecture, discussion and confidential physician audit of practice patterns.…”
Section: Introductionmentioning
confidence: 99%